(untitled) (Medical Forum Monthly, 2024)
Objective: To observe and evaluate the structural changes in the stomach of the offsprings of Swiss albino mice exposed to smokeless tobacco during pregnancy. Study Design: Observational / descriptive study. Place and Duration of Study: This study was conducted at the Animal House of Al-TibriMedical College Karachi from July 2015 to December 2015. Materials and Methods: Female albino mice were mated. After confirmation of pregnancy 20 pregnant mice were divided into two groups of 10 each. Group A experimental was given 5% tobacco of local brand mixed with their normal chow diet along with clean water ad libitum and group B control was given normal diet along with clean water ad libitum. After 2 weeks of birth, 20 offsprings (10 male and 10 female) were selected randomly from both groups. The offsprings were sacrificed by cervical dislocation and their stomachs were removed for gross and histological analysis. Results: The mean weight of stomach in experimental male offspring was found to be 0.12±0.01 grams, while in control group it was 0.18±0.02 grams. Whereas the mean weight of stomach in experimental female was found to be 0.10±0.02. However in control female group it was observed as 0.15±0.02 grams. The difference in the mean weight of stomach between the experimental and control groups was observed to be highly significance (p Value < 0.001) in both male and female offspring. The infection induce marked changes in the stomach, like destruction of gastric folds and glands, desquamation of endothelial cells of glands. Mild to moderate inflammatory and chronic necrotic changes with gastric atrophy were observed in microscopic findings of the gastric mucosa in smokeless tobacco treated animals. Mild dysplasia and adenomatous changes were seen in few cases of experimental animals. This lesion may result from the oral administration of toxic irritants. Conclusion: The use of smokeless tobacco during pregnancy has some adverse outcomes on the offspring of mice manifested by the decrease in stomach weight as well as alter the histological features of stomach mucosa especially produces the fatty infiltration, necrotic and adenomatous changes of the gastric glands.